Identifying Students’ Error in Writing Islamic Text at the Third Semester of English Study Program at IAIN Bone - Abdul Rahman (Universitas Cokroaminoto Palopo, 2019)
This research aimed to find out the most common errors do the students made in their writing Islamic text at the third semester of English Study program IAIN Bone in Academic Years 2018-2019. The data were collected from the students’ writing of the third semester. The key instrument used was writing test result and interview. This research used descriptive research. It refers to the descriptive qualitative. Qualitative data described each category that occurred in the students’ writing. The researcher described the situation about the occurrence of the errors in the students’ writing. The total number of lexical errors that the researcher found in the students’ writing Islamic text was 150 errors that consisted of lexicon category was 68 errors and surface strategy was 82 errors. Most of the students’ errors in the lexical category were sentence pattern. Sentence pattern is the highest errors made by the students in writing Islamic text with 10 students or 62.50% made errors; the second was punctuation and article by 5 students or 31.25%; the third errors in spelling by 4 students or 25%; the fourth errors in vocabulary and preposition by 3 students or 18.75%; the last errors in tense, pronoun, and conjunction by 1 student or 6.25%. It is figured out that the students have less ability in writing a text and still have difficulties in learning grammatical structures in writing process.